PENGARUH PERAN MASYARAKAT MADANI DAN SISTEM PENGENDALIAN INTERN TERHADAP OPINI AUDIT LAPORAN KEUANGAN PEMERINTAH DAERAH (STUDI PADA KABUPATEN/KOTA DI PROVINSI ACEH) - Surya, Juanda; Suparno, Suparno (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2019)
The purpose of this study is to examine the influence of civil society roles proxyed by human development index variables, community education level, and income level of the community, and internal control system to audit opinion of local government financial report on districts / cities in Aceh Province. The method used in this research is census method. The data used are secondary data in the form of human development index data, income level of society, level of public education and report of examination result of Supreme Audit Board of Republic Indonesia. Objects in this study are all districts/cities in Aceh Province which consists of 18 districts and 5 cities. The analysis used is logistic regression analysis. The results of this study indicate that (1) the human development index influence on the audit opinion of the local government financial report (2) the education level of the community influences on the audit opinion of the local government financial report (3) the income level of society influences on the audit opinion of local government financial report (4) The internal control system influence on the audit opinion of local government financial report